Refugees entered the labor market later than other migrants - Zerrin Salikutluk; Johannes Giesecke; Martin Kroh (DIW Economic Bulletin, 2016)
It has taken longer for refugees who have been living in Germany for some time, particularly those who arrived between 1990 and 2010, to take up gainful employment than other migrants. These findings are based on data from the Socio-Economic Panel (SOEP) and the IAB-SOEP Migration Sample. In addition, these refugees show a higher rate of unemployment and earn lower incomes by comparison even years after arriving in Germany. Refugees from different regions also show a tendency to work in certain occupations and in jobs that are below their skill levels. These findings indicate the importance of targeted educational and labor market measures to facilitate the best possible integration of refugees into the German labor market-and thereby also into German society.
Keywords: J01; J15; J6; 330